No clinical benefit of rapid versus gradual tapering of immunosuppression to treat sustained BK virus viremia after kidney transplantation: a single‐center experience. (11th January 2019) - Devresse, Arnaud; Tinel, Claire; Vermorel, Agathe; Snanoudj, Renaud; Morin, Lise; Avettand‐Fenoel, Véronique; Amrouche, Lucile; Scemla, Anne; Zuber, Julien; Legendre, Christophe; Rabant, Marion; Anglicheau, Dany
Summary: Immunosuppressive drug tapering is currently the recommended treatment of BK virus (BKV) viremia after kidney transplantation; however, its exact modalities remain unclear. We retrospectively compared two consecutive strategies in 111 patients with sustained viremia: a gradual monitoring/tapering group (GT, n = 57) before 2012 and a rapid monitoring/tapering group (RT, n = 54) after 2012. At viremia diagnosis, the dose of mycophenolic acid (MPA) and tacrolimus levels (T0 ) were similar among patient groups. However, following onset, the dose of MPA at 1 month ( P  = 0.002) and 3 months ( P  = 0.005) and Tac T0 at 1 month ( P  = 0.030) and 3 months ( P  = 0.006) were lower in the RT group. This rapid minimization shortened BKV viremia ( P  < 0.001) and resulted in a better protection of graft function in patients with confirmed BKV‐associated nephropathy ( P  = 0.033) without impacting 5‐year graft survival. Survival without rejection was similar ( P  = 0.571), but the RT group had increased the development of de novo donor‐specific antibodies (dnDSAs; P  < 0.001). Multivariate Cox analysis identified basiliximab versus Thymoglobulin ® induction [hazard ratio (HR), 3.090; P  = 0.001] and the RT strategy (HR, 6.021; P  = 0.002) as independently associated with dnDSAs. Compared to a gradual tapering, rapid immunosuppression tapering to treat sustained BKV viremia does not improve medium‐term clinical outcome but increases the risk of developing dnDSAs.